The existence of audit expectation gap in Malaysia / Mohd Ariff Kasim and Siti Rosmaini Mohd Hanafi - Kasim, Mohd Ariff; Mohd Hanafi, Siti Rosmaini (Accounting Research Institute (ARI) & Faculty of Accountancy, 2008)
This study is an extension of the authors' previous study which was conducted at Universiti Tenaga Nasional (UNITEN) in 2005 on the effect of undergraduate audit education in reducing audit expectation gap. The present study aimed to provide greater empirical evidence on the existence of audit expectation gap in Malaysia. The methodology was developed based on Gramling and Schazberg's (1996) study. Aninstrument of audit expectation gap was distributed to auditors, accountants and accounting educators in Malaysia to ascertain whether there was evidence on the existence of an audit expectation gap between these groups of respondents. The results indicated the existence of an audit expectation gap between auditors, accountants and accounting educators.